1987
DOI: 10.1104/pp.85.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Accumulation of the Herbicides Chlorsulfuron and Clopyralid in Excised Pea Root Tissue

Abstract: The herbicides chlorsulfuron and clopyralid were taken up rapidly by excised pea root tissue and accumulated in the tissue to concentrations ten and four times those in the external medium, respectively. Uptake was related linearly to external herbicide concentration over a wide concentration range, implying that transport across the membrane is by nonfacilitated diffusion. Uptake of both compounds was influenced by pH, with greatest uptake at low pH. The pH dependence of uptake suggests that the herbicides (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 11 publications
5
44
0
2
Order By: Relevance
“…This increase in sugars in herbicide-treated leaves has also been reported for imazapyr (21), an imidazolinone-type herbicide known to inhibit ALS (20). On the basis of the mass flow hypothesis of phloem transport, it can be assumed that (6,11). The fact that the chlorsulfuron-induced decrease in assimilate transport also occurs in excised leaves strongly suggests that the herbicide has an effect on the transport of assimilates into the phloem in the source tissue rather than an effect in the sink tissue.…”
Section: Assimilate Transportsupporting
confidence: 59%
See 2 more Smart Citations
“…This increase in sugars in herbicide-treated leaves has also been reported for imazapyr (21), an imidazolinone-type herbicide known to inhibit ALS (20). On the basis of the mass flow hypothesis of phloem transport, it can be assumed that (6,11). The fact that the chlorsulfuron-induced decrease in assimilate transport also occurs in excised leaves strongly suggests that the herbicide has an effect on the transport of assimilates into the phloem in the source tissue rather than an effect in the sink tissue.…”
Section: Assimilate Transportsupporting
confidence: 59%
“…Devine et al (6) have suggested that on the basis of its physicalchemical properties chlorsulfuron should be translocated more readily than it is in whole plants. Assuming that chlorsulfuron has no direct effect on the loading of herbicide molecules into the phloem tissue, i.e.…”
Section: Assimilate Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation by plant cells and tissues of herbicides that are weak acids was found to be greater at the pH close to the pKa of each herbicide (6,7,17,23). Natural compounds which are either weak acids (1) or weak bases (1 1) have also been shown to accumulate differentially in response to pH, and ion trapping has been suggested to at least partially explain accumulation of those compounds by plant cells.…”
Section: Metabolic Inhibitorsmentioning
confidence: 99%
“…Absorption through the symplast and translocation through the phloem are essential for activity. The uptake of clopyralid has been classified as nonfacilitated diffusion by Devine et al (1987) apacentamiento realizados en Norte America muestran que la disponibilidad de plantas toxicas y las perdidas por muerte de ganado a causa de este tipo de plantas estan estrechamente asociadas con la intensidad de apacentamiento. Los estudios revisados muestran que bajo apacentamiento moderado las perdidas por muerte de ganado debido a plantas toxicas promedian aproximadamente 2.0%, comparado con 4.8% bajo intensidades de apacentamiento fuerte.…”
Section: Translocation 24 Hours After Herbicide Applicationunclassified